UJI STABILITAS FORMULASI FACE TONER EKSTRAK DAUN PEGAGAN (Centella asiatica) DENGAN VARIASI KONSENTRASI GLISERIN - Rumanis Afifah; Gigih Kenanga Sari; Maulita Saraswati (Joseph: Journal of Science and Pharmacy, 2025)
Background: The cosmetics industry continues to grow with increasing interest in natural ingredients. Gotu kola leaves (Centella Asiatica) contain bioactive compounds with antioxidant, anti-inflammatory, and skin repair effects, making them potential ingredients for face toners. Toners refresh and balance the skin's pH, while glycerin acts as a humectant to maintain moisture, but its concentration affects the stability and comfort of the preparation. This study formulated a gotu kola extract face toner with varying glycerin concentrations and evaluated its stability through a cycling test (±4 °C and ±40 °C, six cycles). This test is important for assessing the physical and chemical quality of the product while meeting cosmetic registration requirements. Purpose: 1.To determine the compounds contained in gotu kola leaf extract (Centella Asiatica). 2. To determine whether there is an effect on physical quality and stability in variations of glycerin in gotu kola leaf extract (Centella Asiatica) face toner formulations. 3. To determine the face toner formulation that has good stability with variations in glycerin concentration.. Method: Pegagan leaves (Centella asiatica) were extracted using the maceration method with 70% ethanol solvent.   The extract obtained was subjected to phytochemical testing and TLC testing, followed by the preparation of formulations according to the predetermined formulation. A cycling test was conducted for 12 days with 6 cycles, followed by physical quality testing of the face toner formulation.Results: Pegagan extract compounds contain alkaloids, flavonoids, and tannins. There were no significant differences between formulations 1, 2, and 3 with variations in humectants (glycerin). Formulation F2 showed the most optimal stability because both viscosity and pH were relatively stable during six storage cycles. Conclusion: Based on this study, it was found that face toner preparations containing gotu kola leaf extract (Centella Asiatica) at concentrations of 2%, 4%, and 6% had fairly good physical stability parameters.